JUDICIAL COMPLEX STRATEGIES IN HUNGARIAN COURTROOMINTERROGATION - VARGA, Marianna (Comparative Legilinguistics, 2019)
Taking into consideration the characteristics of the Hungarian culture, language and legal system, this paper aims to study complex interrogation strategies used by Hungarian judges. This research is based on my corpus consisting of 10 Hungarian criminal trials recorded by a voice recorder, and written notes from direct observations. The analysis has a complex nature, since it relies on the results of (1) linguistics, because the main goal is to present effective interrogation strategies (2) law, because it is crucial to start the research with understanding the function of the discourse type being analysed:the question strategies are intrinsically connected to the institutional role and the legal system by nature, and (3) psychology has also a great role in the investigation of interrogation in two main aspects: the testimony is based on memories and interrogation has an interpersonal part which should not be omitted in discovering the effective question strategies. This research offers rare data to the courtroom interrogation strategies and the results may also have a significant role in legal practice.